Laser performance of the SG-III laser facility. (13th July 2016) - Zheng, Wanguo; Wei, Xiaofeng; Zhu, Qihua; Jing, Feng; Hu, Dongxia; Su, Jingqin; Zheng, Kuixing; Yuan, Xiaodong; Zhou, Hai; Dai, Wanjun; Zhou, Wei; Wang, Fang; et al.
Abstract : SG-III laser facility is now the largest laser driver for inertial confinement fusion research in China. The whole laser facility can deliver 180 kJ energy and 60 TW power ultraviolet laser onto target, with power balance better than 10%. We review the laser system and introduce the SG-III laser performance here.